POLA PEMANFAATAN LAHAN PESISIR UNTUK KESEJAHTERAAN MASYARAKAT PESISIR DI BANTUL, DAERAH ISTIMEWA YOGYAKARTA - Widyaputra, Primanda Kiky; Setyaningrum, Agustina (Public Sphere: Jurnal Sosial Politik, Pemerintahan dan Hukum, 2024)
The coastal community in Bantul, Special Region of Yogyakarta, possesses a rich coastal ecosystem abundant in natural resources and land potential that can support community well-being. Therefore, understanding the relationship between coastal land utilization and the well-being of the population in Bantul is essential for designing sustainable development policies and programs in the region. This research aims to analyze the patterns of coastal land utilization contributing to the well-being of the coastal community in Bantul. Employing a qualitative approach with literature review and descriptive analysis, secondary data were gathered from various sources such as government reports, scientific journal publications, and relevant previous research. The results indicate indications that the well-being of the coastal community in Bantul is influenced by several factors, including per capita income, access to education and health services, and participation in decision-making. Additionally, sustainable coastal land management is identified as crucial to improving well-being and ensuring the sustainability of natural resources. The research also reveals that the utilization of coastal land for sectors such as fisheries, agriculture, tourism, and industry significantly contributes to the well-being of the coastal community. The well-being of the coastal community in Bantul is closely linked to sustainable coastal land utilization. In efforts to enhance community well-being and preserve coastal ecosystem, an integrated approach involving the government, community, and relevant sectors is necessary. The success of sustainable development in Bantul will depend on appropriate policies and strategies in managing natural resources wisely, protecting the environment, and enhancing the well-being of the coastal community. ABSTRAKMasyarakat di pesisir Bantul, Daerah Istimewa Yogyakarta, memiliki ekosistem pesisir yang kaya akan sumber daya alam dan potensi lahan yang dapat mendukung kesejahteraan masyarakat. Oleh karena itu, memahami hubungan antara pemanfaatan lahan pesisir dan kesejahteraan masyarakat di Bantul menjadi esensial untuk merancang kebijakan dan program pembangunan yang berkelanjutan di wilayah tersebut. Penelitian ini bertujuan untuk menganalisis pola pemanfaatan lahan pesisir yang berkontribusi terhadap kesejahteraan masyarakat pesisir di Bantul. Penelitian ini menggunakan pendekatan kualitatif dengan studi literatur dan analisis deskriptif. Data sekunder diperoleh melalui berbagai sumber seperti laporan pemerintah, publikasi jurnal ilmiah, dan penelitian terdahulu yang relevan dengan topik penelitian. Hasil penelitian menunjukkan adanya indikasi bahwa tingkat kesejahteraan masyarakat pesisir di Bantul dipengaruhi oleh beberapa faktor, termasuk pendapatan per kapita, akses terhadap layanan pendidikan dan kesehatan, serta partisipasi dalam pengambilan keputusan. Selain itu, pengelolaan lahan pesisir yang berkelanjutan menjadi kunci dalam meningkatkan kesejahteraan dan memastikan keberlanjutan sumber daya alam. Penelitian ini juga mengungkapkan bahwa pemanfaatan lahan pesisir untuk sektor perikanan, pertanian, pariwisata, dan industri memberikan kontribusi signifikan terhadap kesejahteraan masyarakat pesisir. Kesejahteraan masyarakat pesisir di Bantul sangat terkait dengan pemanfaatan lahan pesisir yang berkelanjutan. Dalam upaya meningkatkan kesejahteraan masyarakat dan pelestarian ekosistem pesisir, diperlukan pendekatan terpadu yang melibatkan pemerintah, masyarakat, dan sektor terkait. Keberhasilan pembangunan berkelanjutan di Bantul akan tergantung pada kebijakan dan strategi yang tepat dalam mengelola sumber daya alam secara bijaksana, melindungi lingkungan, dan meningkatkan kesejahteraan masyarakat pesisir